JURIDICAL ANALYSIS OF HOLDING STATE-OWNED ENTERPRISES IN THE VIEW OF CORPORATE LAW AND COMPETITION LAW - Selia Putri (Syiah Kuala Law Journal, 2022)
This research aims to analyse the status and Position of subsidiaries company of Holding State-Owned Enterprises and to find out regulate of Holding State-owned Enterprises in the view of Corporate Law and Competition Law. The result showed that Subsidiaries of Holding Stateowned Enterprises have a different status from State-owned Enterprises and have the same position as SOEs in certain aspects. This is based on Article 2A paragraph (7) of Government Regulation No. 72 of 2016, which states that SOEs Holding Subsidiaries are treated the same as SOEs in terms of (1) obtaining government assignments or performing public services; and/or (2) obtaining special State and/or Government policies, including in the management of Natural Resources, with special treatment certain conditions as applied to SOEs. The regulation of SOE holdings, Government Regulation No. 72 of 2016, does not comply with Article 51 Prohibition of Monopolistic Practice and Unfair Competition Law No. 5 of 1999. This is based on the implementation guidelines of Article 51 of Act No. 5 of 1999 State concentration of activities or monopolies cannot be regulated by government regulations, but shall be regulated by law.